EVOLUSI PERAN PEREMPUAN DALAM POLITIK DI ERA GLOBALISASI [EVOLUTION OF WOMEN'S ROLE ON POLITICS IN THE ERA OF GLOBALIZATION] - Elyzabeth Bonethe Nasution; Junika Gozal; Monica Kirana (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2020)
Feminism Theory was born because of the inequality between men’s and women’s rights. Women rejects the popular ideas and opinions saying that their tasks are just handling works around the house, kitchen, husband, and their children. It seems like women’s rights in other fields are just avoided and unacknowledged. In a patriarchy world, women are just objects that could not have any opinions and ideas. So, sometimes women are treated unfairly, especially in the world of politics. As a reaction to that, the waves of Feminism exist. This wave exists in four different types of waves, with one of them is to fight for women’s rights in the world of politics. Globalization, the thing that responsible for the connectivity of the world and easing the flow of information, helps developing the Feminist movement and drives women to have a better awareness of their rights. This research uses historical comparative method, executed by collecting references related to the theme of the research and then comparing it. Based on the results of the research, it shows that the more integrated world, thanks to globalization, plays the role as the drive behind the development of women’s role in the world of politics as well. Bahasa Indonesia Abstract: Teori Feminisme lahir karena adanya kondisi tidak berimbang antara hak laki-laki dan perempuan. Kaum perempuan menolak untuk menerima pendapat yang telah melekat, bahwa tugasnya hanyalah mengurus rumah, dapur, suami dan anak saja. Hak para perempuan di bidang lain seakan-akan diabaikan dan tidak diakui. Dalam dunia yang patrialis, perempuan hanyalah objek yang tidak boleh memiliki pendapat dan tidak boleh berpendapat, sehingga sering kali masih mendapat ketidakadilan, salah satunya dalam bidang politik. Sebagai reaksi terhadap hal tersebut, timbul gelombang Feminisme. Gelombang Feminisme timbul dalam empat gelombang, yang antara lain memperjuangkan hak perempuan di bidang politik. Globalisasi, yang telah membuat dunia terhubung satu sama lain dan memperlancar informasi yang ada, telah membantu memperbesar gerakan feminis dan menggerakkan banyak kaum perempuan untuk sadar akan haknya. Penelitian ini menggunakan metode historis komparatif yang dilakukan dengan cara mengumpulkan referensi-referensi yang berkaitan erat dengan tema makalah dan membandingkannya. Berdasarkan hasil penelitian terlihat bahwa semakin terintegrasinya dunia melalui globalisasi turut menjadi dorongan atas perkembangan bagi peran perempuan dalam bidang politik.